Genetic diversity of wild and cultivated Coffea canephora in northeastern DR Congo and the implications for conservation. Issue 12 (22nd December 2021) - Vanden Abeele, Samuel; Janssens, Steven B.; Asimonyio Anio, Justin; Bawin, Yves; Depecker, Jonas; Kambale, Bienfait; Mwanga Mwanga, Ithé; Ebele, Tshimi; Ntore, Salvator; Stoffelen, Piet; Vandelook, Filip
Abstract: Premise: Many cultivated coffee varieties descend from Coffea canephora, commonly known as Robusta coffee. The Congo Basin has a century‐long history of Robusta coffee cultivation and breeding, and is hypothesized to be the region of origin of many of the cultivated Robusta varieties. Since little is known about the genetic composition of C. canephora in this region, we assessed the genetic diversity of wild and cultivated C. canephora shrubs in the Democratic Republic of the Congo. Methods: Using 18 microsatellite markers, we studied the genetic composition of wild and backyard‐grown C. canephora shrubs in the Tshopo and Ituri provinces and multiple accessions from the INERA Yangambi Coffee Collection. We assessed genetic clustering patterns, genetic diversity, and genetic differentiation between populations. Results: Genetic differentiation was relatively strong between wild and cultivated C. canephora shrubs, and both gene pools harbored multiple unique alleles. Strong genetic differentiation was also observed between wild populations. The level of genetic diversity in wild populations was similar to that of the INERA Yangambi Coffee Collection, but local wild genotypes were mostly missing from that collection. Shrubs grown in the backyards were genetically similar to the breeding material from INERA Yangambi. Conclusions: Most C. canephora that is grown in local backyards originated from INERA breeding programs, while a few shrubs were obtained directly from surrounding forests. The INERA Yangambi Coffee Collection could benefit from an enrichment with local wild genotypes to increase the genetic resources available for breeding purposes and to support ex situ conservation.